Ability of magnetocardiography to detect regional dominant frequencies of atrial fibrillation. Issue 6 (9th June 2015) - Yoshida, Kentaro; Ogata, Kuniomi; Inaba, Takeshi; Nakazawa, Yoko; Ito, Yoko; Yamaguchi, Iwao; Kandori, Akihiko; Aonuma, Kazutaka
Abstract: Background: Lead V1 on electrocardiography (ECG) can detect the dominant frequency (DF) of atrial fibrillation (AF) in the right atrium (RA). Paroxysmal AF is characterized by a frequency gradient from the left atrium (LA) to the right atrium (RA). We examined the ability of magnetocardiography (MCG) to detect regional DFs in both the atria. Methods: Study subjects comprised 18 consecutive patients referred for catheter ablation of persistent AF. An MCG system with 64 magnetic sensors was used to perform MCG in the frontal, lateral, and back planes prior to the ablation procedure in each patient. DFMCG and organization index (OIMCG ) were calculated using fast Fourier transformation. Intracardiac electrograms (ICEs) in both the atria and the coronary sinus (CS) were mapped at 17 sites. Regional DFsICE were also determined. Results: Mean LA DFICE was higher than mean RA DFICE (6.40±0.66 versus 6.16±0.80 Hz, P =0.03). DFMCG in the channel having the highest OIMCG was 6.61±0.88 Hz in the frontal plane, 6.52±0.64 Hz in the lateral plane, and 6.42±0.62 Hz in the back plane ( P =0.3). In each plane, DFMCG correlated with DFICE at the RA appendage ( R =0.95, P <0.0001), the LA appendage ( R =0.91, P <0.0001), and the CS ( R =0.93, P <0.0001). DFECG in V5 modestly correlated with DFICE at the LA appendage ( R =0.82, P <0.0001). Conclusions: MCG could more precisely detect the DFs in the LA and the CS than ECG. However, the usefulness of pre‐procedural detection of the AF frequency gradient for ablation therapy needs to be evaluated in future prospective studies.